Justice 4.0 Centers and effectiveness of judicial service delivery: access to justice and procedural efficiency in Brazil - Vitor Bezerra, Eudes; Rabelo FranÃ§a, Alexsandro José; Caldas Fiquene Barbosa, José Aristóbulo (Ius Humani. Jornal do direito, 2025)
Digital technologies have triggered significant transformations in the contemporary world and, in Brazil, have also impacted the judicial sector, which faces challenges such as case overload and judicial delay. In response, the Conselho Nacional de JustiÃ§a (CNJ) launched the Justice 4.0 Program and the Justice 4.0 Centers, aiming to modernize the judicial system through the digitalization and decentralization of judicial services, in alignment with the notion of the Democratic Rule of Law, in which access to justice is regarded as a fundamental right to be realized. This article aims to examine the Justice 4.0 Centers and their influence on judicial service delivery, particularly regarding access to justice and procedural speed. That way, it explores how innovations based on information and communication technologies (ICTs) contribute to the modernization of the judiciary and the creation of new conflict resolution mechanisms, also examining the structure and functioning of the Justice 4.0 Centers. The applied methodology is qualitative, based on a bibliographic review of doctrinal sources, legislation, and official CNJ documents published between 2020 and 2024, employing document analysis and literature review. The study concludes by discussing the challenges and limitations of the Justice 4.0 Centers, including issues related to territorial jurisdiction and the need for continuous training of judges and court staff, in addition to technical and cultural obstacles that must be overcome in order to achieve the program's objectives, ensuring that the justice system is inclusive and efficient and reflecting a commitment to the effectiveness of human rights through participatory and adaptive processes.